Selecting a Bachelor of Dental Science Degree in Dental Hygiene: Stories shared from a narrative inquiry. - Kanji, Zul; Pidgeon, Michelle; Nilson, Michelle (Journal of Dental Hygiene, 2019)
Purpose: Little is known regarding why prospective dental hygiene students select a four-year entry-to-practice baccalaureate degree rather than a diploma granting program in Canada. The purpose of this study was to explore motivating influences for selecting an entry-to-practice baccalaureate degree in dental hygiene from the perspective of former students. Methods: This study employed a qualitative narrative inquiry consisting of 20 individual semi-structured interviews with 10 former first-year students of the University of British Columbia's Bachelor of Dental Science (dental hygiene) program. Analysis included deductive and inductive coding, member checking, and researcher memos that facilitated the development of emerging themes. Results: Primary reasons for selecting a Bachelor of Dental Science degree included: expanding career opportunities, access to graduate education, prestige and status of the university, perceived credibility, in addition to family, cultural, and peer influences. Conclusion: Findings reveal insights for educational institutions to better understand the possible factors attracting prospective students to a dental hygiene baccalaureate degree program. This information may also be useful for clinicians practicing with a diploma or associate degree who are considering additional education towards a baccalaureate degree.